Views, knowledge, and practices of hospital pharmacists about using clinical pharmacokinetics to optimize pharmaceutical care services: a cross-sectional study - Ramzi Shawahna; Naser Shraim; Rafeef Aqel (BMC, 2022)
Abstract Background Pharmacokinetics (PK) is often used to optimize individualized dosing regimens of some drugs. This study was conducted to determine views, knowledge, and practices of hospital pharmacists in Palestine about using clinical PK to optimize pharmaceutical care services. Method This study was conducted in a cross-sectional design using a questionnaire. The questionnaire collected information about the nature of PK courses taught to hospital pharmacists, importance, relevance, effectiveness, adequacy, and depth of these courses, adequacy of PK skills, implementing PK knowledge/skills in current practice, and barriers limiting the implementation of PK to optimize pharmaceutical care services for hospitalized patients. The hospital pharmacists were visited in their places of work and were asked to complete the questionnaire in privacy. Categorical data were compared using Kruskal-Wallis test or Mann-Whitney U tests. Results The questionnaire was completed by 145 hospital pharmacists. Of the pharmacists, 84 (57.9%) received basic PK courses, 79 (54.5%) were taught integrated PK courses, and 94 (64.8%) agreed that the PK courses were important to their current practice. Similarly, 85 (57.9%) of the pharmacists were not satisfied with the teaching methods and contents of the PK courses. Pharmacists who obtained their degrees from Palestine were less satisfied with the methods of teaching compared to those who obtained their degrees from foreign countries (p-value = 0.006). Only 25 (17.2%) pharmacists reported frequent use of PK knowledge in their current practice. Lack of practical knowledge and continuing education, poor understanding of PK by pharmacists and other healthcare professionals were identified as barriers limiting the implementation of PK in optimizing pharmaceutical care services to hospitalized patients. Conclusion The hospital pharmacists were generally not satisfied with the way PK courses were taught and expressed difficulty in implementing PK knowledge and skills to improve pharmaceutical care services to hospitalized patients. Integrating PK topics within other relevant courses and adopting more clinically oriented learning methods could improve understanding and implementing PK knowledge and skills in optimizing pharmaceutical services to hospitalized patients. Further studies are still needed to determine the optimal teaching/learning methods that can improve knowledge and skill acquisitions of pharmacists in the area of PK.